"You Have to Have Money to Be Good" - Jen McGovern (University of Kansas Libraries, 2018)
The number of Latina women enrolled in higher education is steadily growing yet the proportion of college student-athletes who identify as Latina has barely changed. This study uses Bourdieu's concepts of economic, cultural, and social capital to explain the small percentage of Latina athletes competing in collegiate sport. Data collected from semi-structured interviews with 31 Latina athletes show that all three forms of capital influence Latinas' early sport opportunities and their experiences with the college recruiting process. Latinas with more economic capital played organized youth sport from an earlier age and participated on elite specialized travel teams. They were also better connected to knowledge about the recruiting process and people who could guide them through that process. Women from lower-income backgrounds had fewer opportunities to develop skill and less assistance with the recruiting process. As a result, sport scholarships are more likely to go to women from upper class backgrounds, reproducing the U.S. class and racial hierarchy and placing Latina women at a disadvantage.